L’episodio di Saladino nei «Diz des sages» del ms. Paris BnF, fr. 821 e i «Conti di antichi cavalieri» (Carte Romanze, 2024)
In the Diz des sages (Paris, BnF, fr. 821), a free rewriting of the second book of the Tresor, there is a brief narrative episode featuring Saladin. The same anecdote is first documented in the Conti di antichi cavalieri and is also present in other texts, but it is always attributed to Henry Plantagenet, known as the Young King. The contribution examines the compiling technique of the anonymous author of the Diz and investigates the relationships that link the episode of Saladin with its other attestations.
Keywords: Saladin; The Young King, Henry Plantagenet; Tresor; Conti di antichi cavalieri; Novellino; Benvenuto da Imola